2023
DOI: 10.1177/00034894231176334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dupilumab on Type 2 Biomarkers in Chronic Rhinosinusitis With Nasal Polyps: SINUS-52 Study Results

Abstract: Objectives: Chronic rhinosinusitis with nasal polyps (CRSwNP), asthma, and non-steroidal anti-inflammatory drug-exacerbated respiratory disease (NSAID-ERD) are frequent coexisting conditions and share type 2 inflammatory pathophysiology, with interleukin (IL)-4 and IL-13 as key cytokines. Dupilumab is a monoclonal antibody that blocks the shared receptor for IL-4 and IL-13. The objective of this analysis was to evaluate dupilumab’s effect on type 2 inflammation biomarkers in patients with CRSwNP with/without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As dupilumab inhibits both IL-4 and IL-13 mediated signaling, it can impact a variety of mechanisms involved in N-ERD pathophysiology ranging from Th2 cell differentiation, ILC2 expansion, mast cell activation to airway smooth muscle cell proliferation 34 . We and others have previously demonstrated that dupilumab leads to a marked downregulation of type 2 mediators in serum and nasal secretions of N-ERD patients over time 14,16,35 . However, here we show for the first time that the same trend is also demonstrable during ASA provocation after twenty-four weeks of dupilumab therapy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As dupilumab inhibits both IL-4 and IL-13 mediated signaling, it can impact a variety of mechanisms involved in N-ERD pathophysiology ranging from Th2 cell differentiation, ILC2 expansion, mast cell activation to airway smooth muscle cell proliferation 34 . We and others have previously demonstrated that dupilumab leads to a marked downregulation of type 2 mediators in serum and nasal secretions of N-ERD patients over time 14,16,35 . However, here we show for the first time that the same trend is also demonstrable during ASA provocation after twenty-four weeks of dupilumab therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Although a reduction of type 2 mediators and associated cell subsets was observed in the chronic phase of the disease in patients undergoing therapy with the respective antibodies 15,16 , these studies have not addressed the impact of treatment on cytokine dynamics during acute hypersensitivity reactions. In this regards, data on immune kinetics following ASA challenges are scarce and indicate an increase in systemic proinflammatory IL-6 17 and nasal eosinophils as well as ILC2 influx as early as one hour after provocation, but no increase in serum chemotactic proteins such Eotaxin-1 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Dupilumab is approved for the treatment of uncontrolled CRSwNP in adults and for other allergic diseases, including certain types of moderate-to-severe asthma, moderate-to-severe AD, eosinophilic esophagitis, and prurigo nodularis ( 74 ). Biomarker analysis has revealed that dupilumab treatment in patients with CRSwNP reduced concentrations of type 2 inflammatory biomarkers including eotaxin-3, periostin, eosinophil cationic protein (ECP), and IL-5 in nasal secretions, eotaxin-3, thymus and activation-regulated chemokine, periostin, and total IgE in blood, and leukotriene E4 in urine ( 75 , 76 ). Dupilumab has also been found to downregulate local IgE production and eosinophil homing ( 66 ), and to decrease inflammatory eicosanoid levels and increase levels of anti-inflammatory prostaglandin E 2 ( 77 ).…”
Section: Therapeutic Targeting Of the Key Drivers Of Type 2 Inflammat...mentioning
confidence: 99%
“…The reduction in these biomarkers is similar or greater in subgroups with asthma and AERD, as evidenced in a post-hoc analysis of the SINUS-24 study. 71 …”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Several randomized, placebo-controlled clinical trials have been published involving patients with uncontrolled persistent asthma despite adequate treatment with inhaled corticosteroids and long-acting beta-agonists, 71 , 72 inhaled corticosteroids +1 or 2 rescue medications, 75 or oral corticosteroids. 76 …”
Section: Experience In Other Respiratory Diseasesmentioning
confidence: 99%